Coupled Vibrations in Index-Identified Carbon Nanotubes. Issue 1700 (2014) - Levshov, Dmitry; Michel, Thierry; Paillet, Matthieu; Than, Xuan Tinh; Tran, Huy Nam; Arenal, Raul; Rahmani, Abdelali; Boutahir, Mourad; Zahab, Ahmed-Azmi; Sauvajol, Jean-Louis
ABSTRACT: Combining high resolution transmission electron spectroscopy, electron diffraction, and resonant Raman spectroscopy experiments on the same suspended (free-standing) individual carbon nanotubes is the ultimate approach to relate unambiguously the structure and the intrinsic phonon features of these nano-systems. By using this approach, the effect of coupling between nanotubes on the phonons is investigated in two model nano-systems: (i) a bundle of two non-identical SWNTs (inhomogeneous dimer), (ii) double-walled carbon nanotubes.